Current animal models of hemophilia: the state of the art. Issue 1 (October 2016) - Yen, Ching-Tzu; Fan, Meng-Ni; Yang, Yung-Li; Chou, Sheng-Chieh; Yu, I-Shing; Lin, Shu-Wha
Abstract Hemophilia is the most well-known hereditary bleeding disorder, with an incidence of one in every 5000 to 30, 000 males worldwide. The disease is treated by infusion of protein products on demand and as prophylaxis. Although these therapies have been very successful, some challenging and unresolved tasks remain, such as reducing bleeding rates, presence of target joints and/or established joint damage, eliminating the development of inhibitors, and increasing the success rate of immune-tolerance induction (ITI). Many preclinical trials are carried out on animal models for hemophilia generated by the hemophilia research community, which in turn enable prospective clinical trials aiming to tackle these challenges. Suitable animal models are needed for greater advances in treating hemophilia, such as the development of better models for evaluation of the efficacy and safety of long-acting products, more powerful gene therapy vectors than are currently available, and successful ITI strategies. Mice, dogs, and pigs are the most commonly used animal models for hemophilia. With the advent of the nuclease method for genome editing, namely the CRISPR/Cas9 system, it is now possible to create animal models for hemophilia other than mice in a short period of time. This review presents currently available animal models for hemophilia, and discusses the importance of animal models for the development of better treatment options for hemophilia.